Analysis of hygroscopic growth properties of soluble aerosol under severe nuclear accidents conditions. (September 2020) - Li, Yingzhi; Zhou, Yanmin; Sun, Zhongning; Gu, Haifeng; Ma, Qianchao; Diao, Han
Abstract: Radioactive aerosol released under severe nuclear accidents conditions contains large amounts of soluble compounds. The hygroscopic growth of soluble aerosol enable to enlarge the particle size and affect the subsequent deposition behavior, which plays an important role on source term analysis. However, the investigation about hygroscopic growth properties of typical nuclear aerosol viz. Cesium iodine and cesium hydroxide, has been largely lacking and the hygroscopic model in MELCOR also need to validate and evaluate. In this paper, steady-state hygroscopic model based on Köhler theory was used to predict the hygroscopic growth factors of these two kinds of aerosols. Sensitivity analysis of surface tension and water activity of aqueous-solution droplet on hygroscopic growth factor were performed, and the prediction results were compared with the experimental data to evaluate MELCOR. The results show that the simplification of replacing surface tension of salt droplet with pure water in MELCOR is acceptable. The processing method of water activity in MELCOR overestimates the hygroscopic growth factors of cesium hydroxide, while its predictions are much close to the hygroscopic growth factors of cesium iodine. The improved model has higher prediction accuracy than MELCOR. In addition, the transient hygroscopic growth rate model was also used to analyze the effects of operating parameters on the hygroscopic growth characteristics of soluble aerosol. The hygroscopic growth rate is proportional to the relative humidity, particle size and gas temperature. Aerosol particles with larger initial size under higher relative humidity condition require longer time to attain equilibrium state, and the equilibrium time decreases with the increasing gas temperature. This study can provide theoretical reference for fundamental understanding of hygroscopic growth properties of soluble aerosol and the estimation of aerosol source terms under severe nuclear accidents conditions. Graphical abstract: Image 1 Highlights: The hygroscopic model in MELCOR is validated and evaluated. The improved hygroscopic model has higher prediction accuracy than MELCOR. The transient hygroscopic growth characteristics are systematically analyzed under different operation conditions.